Normothermic with or without hypothermic oxygenated perfusion for DCD before liver transplantation: European multicentric experience. Issue 11 (12th September 2021) - Maroni, Lorenzo; Musa, Nicola; Ravaioli, Matteo; Dondossola, Daniele Eliseo; Germinario, Giuliana; Sulpice, Laurent; Cescon, Matteo; Rossi, Giorgio Ettore; Boudjema, Karim
Abstract: Grafts from donors with cardiac death (DCD) are subject to warm ischemia time (WIT) due to the no‐touch‐period (20 min in Italy and 5 min in France). These livers (LT) have higher rates of early allograft dysfunction (EAD), primary non‐function (PNF), and ischemic cholangiopathy (IC) compared to LT from brain dead donors (DBD). Normothermic regional perfusion (NRP) is a beneficial strategy to mitigate organ damage; a further approach is the application of ex vivo hypothermic oxygenated perfusion (HOPE) after cold storage (CS). We retrospectively analyzed LTs performed from 2016 to 2019 at three transplant centers using NRP‐DCD grafts: Bologna and Milan treated with HOPE (group A), Rennes preserved using CS (group B). No‐flow period, total and functional WIT were significantly higher in group A than in group B (30.5±7.7 vs. 20.5±4.1; 56.5±20.4 vs. 39.1±21.6; 41.9±12.5 vs. 25.5±3.7; respectively, P < .05), without differences in the postoperative course. In particular, the two groups had similar rates of EAD (21.1% vs. 25.0%), PNF (5.3% vs. 6.3%), IC (0% vs. 12.5%, P = .112), and non‐IC biliary complications (0% vs. 6.3%, P = .457), re‐LT (10.5% vs.12.5%). This occurred despite a high rate of UK DCD risk score > 10 (63.2% A vs. 17.6% B, P = .000), which theoretically would make a large number of these transplants "futile." In conclusion, Italian and French groups had similar post‐LT outcomes, probably related to the use of HOPE after CS in the case of long WIT.